PERAMALAN TREND KUNJUNGAN WISATAWAN DIKAWASAN KONSERVASI MANGROVE BEKANTAN (KKMB) DI KOTA TARAKAN - Galih Yogi Rahajeng; Arni Arni (J-PEN Borneo : Jurnal Ilmu Pertanian, 2019)
ABSTRACT Conservation Area for Mangrove and Proboscis in Tarakan City was built to preserve mangrove ecosystems and wildlife in its development and alternative ecotourism destinations. Based on the potential of Conservation Area for Mangrove and Proboscis in Tarakan City, therefore this study aims to predict the trend of tourist visits in Conservation Area for Mangrove and Proboscis in Tarakan City so that it can become the foundation for the development of Conservation Area for Mangrove and Proboscis inTarakan City in the future. In this study using respondents as many as 100 respondents who were Conservation Area for Mangrove and Proboscis in Tarakan City visitors. The sampling used method was accedential sampling and quota sampling. The result shown than visitors of Conservation Area for Mangrove and Proboscis inTarakan from 2018-2022 estimated to reach 164,888,5 visitors. The average decrease in visits per year is 978 people. Because of the facilities in the Conservation Area for Mangrove and Proboscis in Tarakan City are inadequate, such as wooden bridge that begin to be damaged and slippery when it rains, lack of place to sit, cleanliness that has not been maintained, unsanitary toilets, and lack of parking areas, and reduced proboscis monkey. If there is no renovation and repair of facilities, visitors tend not to choose the Conservation Area for Mangrove and Proboscis in Tarakan City as an alternative tourist attractions. Keywords: Conservation of mangrove, Ecotourism, Trend Analysis. ABSTRAK Kawasan Konservasi Mangrove dan Bekantan Kota Tarakan (KKMB) dibangun dan memiliki tujuan sebagai pengembangan satwa liar dan ekowisata alternatif. Berdasarkan potensi yang ada, oleh karena itu maka penelitian ini bertujuan untuk meramalkan trend kunjungan wisatawan di KKMB agar dapat menjadi landasan dalam pengembangan KKMB di masa depan. Dalam penelitian ini menggunakan 100 responden yang merupakan pengunjung KKMB. Metode pengambilan sampel yang digunakan adalah pengambilan sampel akedensial dan kuota. Hasil Penelitian memperlihatkan pengunjung KKMB di Kota Tarakan dari 2018-2022 diperkirakan mencapai 164.888,5 orang. Penurunan rata-rata kunjungan per tahun adalah 978 orang. Karena fasilitas di Kawasan Konservasi Mangrove dan Bekantan Kota Tarakan  tidak memadai, seperti jembatan kayu yang mulai rusak dan licin saat hujan, kurangnya tempat duduk, kebersihan yang belum dijaga, toilet yang tidak bersih, dan kurangnya area parkir, dan  berkurangnya populasi bekantan. Jika tidak ada renovasi dan perbaikan fasilitas, pengunjung cenderung tidak memilih Kawasan Konservasi Mangrove Bekantan di Kota Tarakan sebagai tempat wisata alternatif. Kata kunci: Konservasi mangrove, Ekowisata, Analisis Trend.